2015
DOI: 10.1177/1079063215595404
|View full text |Cite
|
Sign up to set email alerts
|

Changes in J-SOAP-II and SAVRY Scores Over the Course of Residential, Cognitive-Behavioral Treatment for Adolescent Sexual Offending

Abstract: Although the Juvenile Sex Offender Assessment Protocol–II (J-SOAP-II) and the Structured Assessment of Violence Risk in Youth (SAVRY) include an emphasis on dynamic, or modifiable factors, there has been little research on dynamic changes on these tools. To help address this gap, we compared admission and discharge scores of 163 adolescents who attended a residential, cognitive-behavioral treatment program for sexual offending. Based on reliable change indices, one half of youth showed a reliable decrease on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 102 publications
4
24
0
Order By: Relevance
“…This would suggest that the tool is not sufficiently sensitive to measure changes that juvenile offenders experience during their transition through the juvenile justice system. The results of the present study are consistent with the limited number of studies on the measurement of change with SAVRY assessments [9, 12, 13]. This small body of work suggests that SAVRY has difficulties in measuring change in risk/needs of adolescent offenders.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This would suggest that the tool is not sufficiently sensitive to measure changes that juvenile offenders experience during their transition through the juvenile justice system. The results of the present study are consistent with the limited number of studies on the measurement of change with SAVRY assessments [9, 12, 13]. This small body of work suggests that SAVRY has difficulties in measuring change in risk/needs of adolescent offenders.…”
Section: Discussionsupporting
confidence: 88%
“…Unfortunately, there is very little known about the extent to which SAVRY is capable of measuring the changes that juvenile offenders experience during adolescence. In a retrospective study in Canada, Viljoen et al [12] found that approximately one-third part of the sample of 163 juvenile sex offenders, who attended a residential cognitive-behavioural program, showed a decrease in their average scores on the SAVRY dynamic risk items and 8% had an increase on the average scores of the protective items. In a longitudinal study with male ( n = 107) and female ( n = 49) juvenile offenders, Viljoen et al [13] reported that SAVRY reassessments during the probation period were no more predictive than the initial assessment at the start of the probation, suggesting that the average change in risk/needs between the two moments in time had no influence on the predictive validity of the risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with other studies (Draycott et al, 2012;Viljoen et al, 2015), we calculated SEM using interrater reliability, as this is an important form of reliability for risk assessment tools. MDC was calculated as MDC = 1.96 (Beckerman et al, 2001;Statford et al, 1996).…”
Section: Measurement Error and Reliable Change Sem Was Calculated Asmentioning
confidence: 78%
“…Thus far, a study with adolescents in a residential treatment program for sexual offending, found that although SAVRY protective factors increased over the course of treatment, these increases did not translate into reductions in reoffending (Viljoen, Gray, Shaffer, Latzman, et al, 2017). In addition, a prior study from the current sample found that SAVRY protective factors showed some, modest change over time among adolescents on probation, but this study did not use statistical procedures, such as multilevel modelling (MLM), to test if within-individual increases in protective factors predicted subsequent decreases in offending (Viljoen, Shaffer, Gray, & Douglas, 2017).…”
Section: Gaps In Research: the Need For Conceptually Informed Researchmentioning
confidence: 99%